Marine Bacteria Producing L-Asparaginase with Low Glutaminase and Urease Co-Activity from Pangandaran East Coast Indonesia - Pertiwi, Wulan; Namira, Azmy Jasmine; Moeis, Maelita Ramdani; Muharram, Luthfia Hastiani; Hernahadini, Nelis (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
acterial L-asparaginase is a therapeutic enzyme widely used in the treatment of Acute Lymphoblastic Leukemia (ALL). Although L-asparaginase is prominent in treating ALL, its use is limited due to its side effects caused by its dual substrate specificity towards both asparagine and glutamine. This study aimed to isolate and identify marine bacteria from the East Coast of Pangandaran capable of producing L-asparaginase with low glutaminase and urease co-activities. A semi-quantitative approach was employed, involving the isolation and screening of seawater bacteria using Zobell Marine media supplemented with L-asparagine, glutamine or urea and phenol red as a pH indicator to determine the enzymatic activity. Molecular identification was performed by amplifying and sequencing the 16S rRNA gene, followed by phylogenetic analysis using the neighbor-joining method with 1,000 bootstrap replicates. The results indicated that the bacterial isolate designated PT3 exhibited a high enzymatic index of 4.2 for L-asparaginase, surpassing that of the positive control (E. coli), which had an index of 1.4. Sequence analysis revealed that PT3 shared 99.58% identity with Marinobacterium georgiense strain NBRC 102606, an earlier synonym of Marinobacterium iners. Therefore, PT3 was identified as a strain of Marinobacterium iners, with potential as a novel source of L-asparaginase and displayed significant L-asparaginase activity with minimal co-activity of glutaminase and urease, highlighting its potential as a safer alternative for therapeutic enzyme development.